Morphometric analysis of phytoliths: recommendations towards standardization from the International Committee for Phytolith Morphometrics. (April 2016) - Ball, Terry B.; Davis, AnnaLisa; Evett, Rand R.; Ladwig, Jammi L.; Tromp, Monica; Out, Welmoed A.; Portillo, Marta
Abstract: Morphometric analysis (measurements of size and shape) has become a significant research tool in phytolith studies. The International Phytolith Society (IPS) appointed the International Committee for Phytolith Morphometrics (ICPM) to establish methodological standards for the discipline. This paper presents current recommendations of the ICPM. It discusses the role of morphometric analysis in phytolith studies and recommends a paradigm for its application, criteria for data collection and publication, definitions for basic measurements and software for computer-assisted image analysis. Highlights: Recommendations for phytolith morphometric analysis. Phytolith analysis flow chart. Criteria and protocols for phytolith morphometric analysis. Plugins and macros for using ImageJ for phytolith morphometric analysis.